Uncommon type some stories - Hanks, Tom 1956- (William Heinemann, 2017)
A collection of seventeen wonderful short stories showing that two-time Oscar winner Tom Hanks is as talented a writer as he is an actor
Keywords: Typewriters / Fiction; Interpersonal relations / Fiction; Short stories; American fiction